Characteristic of the information sector (in international aspects) - Kėdaitienė, Angelė (Information & Media, 1994)
The purpose of this study is to take a look through information industries (in international context), as a new field of human activities. The beginning of information industries is 1962 when American economist F. Machlup made a try to describe information industry as a field of human activities. The main sector of information industries is production of information technology. There is a lot of statistic data on information technologies in this study.